Perspectives of Blockchain Technology, its Relation to the Cloud and its Potential Role in Computer Science Education - Purdon, I.; Erturk, E. (Engineering, Technology & Applied Science Research, 2017)
Blockchain ledgers and the Cloud are a perfect match. On the one hand, there is an inherent requirement for multiple separate authentication nodes to validate every Blockchain transaction with each node requiring substantial encryption calculation capability. On the other hand, massive economies of scale can bring down the cost per transaction, and provide service continuity. Additionally, the Cloud provides a perfect incubator for proof-of-concept projects. This paper considers the future implications of Blockchain, as the concept of disintermediated trustless ledgers stimulates the imagination of computer scientists and innovators. The Cloud’s role in implementing this new paradigm is also highlighted, as a new decentralized P2P-Cloud model. Finally, this paper discusses how Blockchain may be integrated into the university level computer science and information technology curriculum.